Benson's microbiological applications laboratory manual in general microbiology - Brown, Alfred E. (McGrwa-Hill, 2009)
A microbiology laboratory manual that features 77 self-contained, illustrated exercises, and four-color format. It is suitable for majors and non-majors lab course.